Oxidative stress in cows with prolapsus uteri, caesarean section, and retained placenta - Erisir, M.; Akar, Y.; Gurgoze, S. Yaralioglu; Yuksel, M.; Kaynar, O. (Blackwell Publishing, 2006)
[Abstract Not Available]
31st Congress of the Federation-of-European-Biochemical-Societies (FEBS) -- JUN 24-29, 2006 -- Istanbul, TURKEY